Hallucinations Experienced by Visually Impaired: Charles Bonnet Syndrome - Pang, Linda (Optom Vis Sci, 2016)
Charles Bonnet Syndrome is a condition where visual hallucinations occur as a result of damage along the visual pathway. Patients with Charles Bonnet Syndrome maintain partial or full insight that the hallucinations are not real, absence of psychological conditions, and absence of hallucinations affecting other sensory modalities, while maintaining intact intellectual functioning. Charles Bonnet Syndrome has been well documented in neurologic, geriatric medicine, and psychiatric literature, but there is lack of information in optometric and ophthalmologic literature. Therefore, increased awareness of signs and symptoms associated with Charles Bonnet Syndrome is required among practicing clinicians. This review of the literature will also identify other etiologies of visual hallucinations, pathophysiology of Charles Bonnet Syndrome, and effective management strategies.